Three-Dimensional Arterial Spin Labeling-Guided Sub-Volume Segmentation of Radiotherapy in Adult Non-Enhancing Low-Grade Gliomas - Zhu, Zihong; Gong, Guanzhong; Wang, Lizhen; Su, Ya; Lu, Jie; Yin, Yong (Frontiers in Oncology, 2022)
Objective: The present study aimed to evaluate the feasibility of sub-volume segmentation for radiotherapy planning of adult non-enhancing low-grade gliomas (NE-LGGs) guided by three-dimensional arterial spin labeling (3D-ASL). The differences in high- and low-perfusion areas of NE-LGGs were analyzed by multi-sequence magnetic resonance imaging (MRI) radiomics. Methods: Fifteen adult patients with NE-LGGs were included in the study. MR images, including T1-weighted imaging (T1WI), T2 Propeller, T2 fluid-attenuated inversion recovery (T2 Flair), 3D-ASL, and contrast-enhanced T1WI (CE-T1WI), were obtained. The gross tumor volume (GTV) was delineated according to the hyperintensity on T2 Flair. The GTV was divided into high- and low-perfusion areas, namely GTV-ASL and GTV-SUB, respectively, based on the differences in cerebral blood flow (CBF) value. The volumes and CBF values of high- and low-perfusion areas were measured and compared. The least absolute shrinkage and selection operator (LASSO) regression was used to select the optimal features of all MR maps. Receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic accuracy of the absolute CBFmean (aCBFmean), relative CBFmean (rCBFmean, normalized by the CBF value of the normal gray matter) and screened features in differentiating high- and low-perfusion areas. Results: Among the enrolled patients, 3 (20%) patients with NE-LGGs showed focal intra- and post-radiotherapy contrast enhancement within a prior high- perfusion area of 3D-ASL. The volume ratio of the GTV-ASL to the GTV was (37.08%±17.88) % (46.26±44.51 vs. 167.46±209.64cm3, P=0.000). The CBFmean in the high-perfusion area was approximately two times of that in the edema area or normal gray matter (66.98±18.03 vs. 35.19±7.75 or 33.92±8.48ml/100g/min, P=0.000). 13 features were screened, 7 of which were extracted from 3D-ASL. The area under curve (AUC) values of aCBFmean, rCBFmean and firstorder_10Percentile from 3D-ASL were more than 0.9, of which firstorder_10Percentile was the highest. Their cutoff values were 44.16 ml/100g/min, 1.49 and 31, respectively. Conclusion: The difference of blood perfusion in the GTV can be quantified and analyzed based on 3D-ASL images for NE-LGGs, which could guide the sub-volume segmentation of the GTV. 3D-ASL should become a routine method for NE-LGGs during simulation and radiotherapy.